Strengthening the Molecular Biology Concept of DNA as the Basis for Disease Pathogenesis in MGMP Biology of Malang - Adrianto, Hebert; Lewi Santoso , Jemima; Rambung, Etha; Tabita Hasianna Silitonga, Hanna; Rio Ferdinand, Gede (Community Development Journal, 2025)
Teachers' and students' understanding of the molecular structure of DNA (Deoxyribonucleic acid) is important because it is a fundamental concept that explains the pathogenesis of disease and mutations in cell biology learning. This activity aims to improve Biology teachers' understanding of the molecular structure of DNA. The activity was conducted at SMAN 1 Bululawang Malang, with 39 Biology teachers who were members of Malang's Biology Subject Teachers' Community (MGMP) as participants. The methods used included interactive lectures, group discussions, and case studies on sickle cell anemia. The resources utilized for the community service included laptops connected to Wi-Fi, Google Forms for pre-test and post-test applications, PowerPoint slides for the materials, patient scenario PPT, and laptops. Evaluation was carried out with pre-tests and post-tests to measure the improvement in participants' understanding. The evaluation results showed that participants gave positive feedback regarding the activity. They felt that there was an application of the chemical structure of DNA bands to the shape of DNA, the bioprocess of protein synthesis, and the pathogenesis of sickle cell anemia. A significant increase in conceptual understanding was observed, with an average pre-test score of 67.69 and an average post-test score of 92.05. The five teachers who obtained the highest scores received prizes in the form of medical biology books, which were authored by us. Similar programs are recommended for implementation in other areas to support the improvement of education quality in Indonesia and benefit students who will pursue medical courses.